The Kuleshov Effect and the Death of the Auteur - Michael Russell (University of Edinburgh, 2005)
The 'Kuleshov Effect' has long been regarded as being both of seminal importance in the development of cinema in the 1920s and yet also as being so ambiguous and difficult to interpret that it has almost become all things to all people. This article shall utilise the Kuleshov Effect as its own palimpsest to try to trace connections between Soviet montage cinema, the politique des auteurs of the French Nouvelle Vague and Barthes' essay on 'The Death of the Author'.